Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content: 1. The reality of including the values of knowledge passion in the books of My Eternal Language in the intermediate stage in the Kingdom of Saudi Arabia Dr. Mashael Saleh Al-Dosari , Mrs. Ebtehal Yehya Al-Ahmadi 2. The relationship between algebraic thinking and geometric thinking among second-grade intermediate students Mr. Abdullah Thuwaini Al-Harbi , Co-Prof. Bader Muhammed aldalean 3. The Mastery level of Sixth-grade Female Students in the Kingdom of Saudi Arabia of the Skills of Mathematical Writing and Mathematical Speaking through Electronic Media Mrs. Sarah Abdullah Al-Ghamdi , Dr. Najla Ali Al-Khabti 4. The effectiveness of a program based on the use of Puppet Theater in answering some common children’s questions in early childhood Mrs. Tahani Mater Al-Humaydani 5. The Reality of Teaching Computational Thinking Skills from Viewpoints of Female Computer Teachers in Riyadh City Mrs. Remsh Nasser Alqahtani , Prof. Ahmad Zaid Almassaad 6. The Impact of Teaching Islamic Jurisprudence Using the Strategy of What Do I Know? What Do I Want to Learn? and What Did I Learn? on the Academic Achievement and Development of Critical Thinking Skills among Second-Grade Intermediate Students Mr. Rashid Fayez Al-Asbali , Dr. Omar Abdul-Qadir Al-Shamti 7. Proposed conception for the program of preparing an Islamic education teacher in the primary stage in light of quality standards and academic accreditation Prof. Awad Zuriban Aljohani 8. The reality of creative thinking strategies practice among Arabic language in the Directorate of Education South Hebron Mr. Ashraf Ibraheem Al-Sharha